2023
DOI: 10.1002/jcp.31069
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 regulates mitophagy in liver fibrosis through deacetylation of PINK1/NIPSNAP1

Abstract: Damaged mitochondria, a key factor in liver fibrosis, can be removed by the mitophagy pathway to maintain homeostasis of the intracellular environment to alleviate the development of fibrosis. PINK1 (PTEN‐induced kinase 1) and NIPSNAP1 (nonneuronal SNAP25‐like protein 1), which cooperatively regulate mitophagy, have been predicted to include the sites of lysine acetylation related to SIRT3 (mitochondrial deacetylase sirtuin 3). Our study aimed to discuss whether SIRT3 deacetylates PINK1 and NIPSNAP1 to regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Ultimately, we uncovered that sirt3 expression of the endothelial cells could be upregulated by EVs released from IDO1 high ovarian cancer cells, which is known to play essential roles in regulating mitophagy [ 60 , 73 , 74 ]. Prior studies have shown that acetylation favors protein stabilization [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, we uncovered that sirt3 expression of the endothelial cells could be upregulated by EVs released from IDO1 high ovarian cancer cells, which is known to play essential roles in regulating mitophagy [ 60 , 73 , 74 ]. Prior studies have shown that acetylation favors protein stabilization [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, SIRT4 may also function as a deacetylase in our model. Additionally, Li et al indicated that SIRT3 regulates mitophagy in liver fibrosis through deacetylation of PINK1/NIPSNAP1 74 . In our research, Sirt4 may regulate Pink1 by deacetylating it, thus contributing to the regulation of mitophagy and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Liver inflammation leads to the activation of HSCs, the major source of the fibrous scars in liver fibrosis [ 78 , 101 ]. Damaged mitophagy was demonstrated to be involved in carbon tetrachloride (CCl 4 )- or common bile duct ligation (CBDL)-induced liver fibrosis in rodents [ 102 , 103 , 104 , 105 ]. FK506 binding protein 51 (FKBP51) is a glucocorticoid receptor binding protein that is crucial for modulating metabolic function ( Figure 3 ).…”
Section: Role Of Liver Cell Mitophagy In Masld and Liver Fibrosismentioning
confidence: 99%
“…In PM2.5-induced liver fibrosis, PM2.5 activated ROS-mediated mitophagy and miR-411/Drp1-mediated mitophagy in HSCs [ 111 , 112 ]. In CCl 4 -induced murine liver fibrosis, decreased deacetylase SIRT3 levels are observed, while Sirt3 knockout further exacerbates liver fibrosis [ 105 ]. Mitochondrial SIRT3 specifically deacetylates PINK1 and nonneuronal SNAP25-like protein 1 (NIPSNAP1) to improve impaired mitophagy and attenuate HSC activation and ECM production [ 105 ].…”
Section: Role Of Liver Cell Mitophagy In Masld and Liver Fibrosismentioning
confidence: 99%